Juxtacribrilina mutabilis - Rasmus Martaeng; Matthias Obst; Piotr Kuklinski (University of Gothenburg, 2022)
21 ASVs of Juxtacribrilina mutabilis (Cribrilina mutabilis), 313bp length of CO1 gene.

Acquired from European Autonomous Reef Monitoring Structures by ARMS-MBON programme between 2018 and 2021.
Keywords: Cribrilina mutabilis; Occurrence; Observation; Cribrilina mutabilis; OCCURRENCE; Biological Sciences; Biologi